Results of laser photocoagulation in patients with diabetic retinopathy developed as a complication of diabetes type 2 - Wilczyński, Michał; Dzięgielewski, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: Laser photocoagulation is a widely used method of treatment of diabetic retinopathy. The purpose of the work was to analyze the results of laser photocoagulation of the retina in patients with diabetic retinopathy, as a result of diabetes type 2. Material and methods: The examined group consisted of 129 patients with diabetes type 2, treated in the Regional Centre of Diabetology and Metabolic Diseases in Łódź, who underwent laser photocoagulations as a treatment of diabetic retinopathy. Patients age were 30 to 82 years old (mean age 61), had been treated for diabetes from 1 year to 47 years (mean 17 years). Laser photocoagulations were performed in 258 eyes. The evaluation of results was based on 6 months follow-up examinations after laser treatment and comprised functional results and condition of the eye fundus. Results: In the examined groups simple non proliferative diabetic retinopathy was recognized in 36 eyes (13.95%), preproliferative retinopathy in 158 eyes (61.24%) and proliferative retinopathy in 64 eyes (24.8%). Focal photocoagulations were performed in 103 eyes. Improvement in visual acuity was noted in 82 eyes (79.61%) and stabilization or improvement in the state of the eye fundus in 92 eyes (89.32%). „Grid” photocoagulation was carried out in 73 eyes, improvement in visual acuity was noted in 53 eyes (72.60%) and stabilization or improvement in the state of the eye fundus in 58 eyes (79.45%). Panretinal photocoagulation was performed in 82 eyes. Improvement or stabilization of visual acuity was observed in 46 eyes (46.10%) and stabilization of state of the eye fundus in 54 eyes (65.85%). In cases of patients with non proliferative diabetic retinopathy stabilization of visual acuity was observed in 86.11% of eyes and stabilization of the eye fundus in 94.44% of eyes. In patients with preproliferative diabetic retinopathy stabilization of visual acuity was found in 71.52% of eyes and stabilization of state of the eye fundus in 80.38% of eyes. In cases of patients with proliferative retinopathy the percentages amounted to 57.81% and 67.19%, respectively. Conclusions: The best functional results of laser photocoagulations, as well as stabilization of state of the eye fundus were achieved in patients with non proliferative retinopathy and after focal laser photocoagulations. The least favourable results were achieved in patients with proliferative diabetic retinopathy and in patients after panretinal photocoagulations. It probably results from the intensity of retinal lesions, which were an indication for these types of photocoagulations. The achieved improvement was greater regarding anatomical results, when compared to functional results. In order, to prevent the development of diabetic lesions in the eye fundus, it is necessary to carry out regular ophthalmologic check-ups, to qualify patients for laser photocoagulations, as early as possible.